O fascínio do dever para os cristãos: estudos em Gálatas e na história da igreja - Kepler, Karl Heinz (2013)
In this work we try to discover and understand why in spite of New Testament teachings a large part of the Church still guides the life of Christians based on the obligation to obey Christian duties, laws, and rules similarly to what happened to the Galatians at the time Paul wrote his Letter to them. The first part studies briefly the moral of duty in Christianity through History and the historical fight between the moralities of duty and pleasure. In that respect, we look to Jewish Old-Testament context, to Greek cultural context, and to the teachings and attitudes of Jesus, Paul, and the Church over the centuries in an effort to establish when and in which situation the morality of duty became hegemonic among Christians. This historical approach of the first part follows the development of the morality of duty also into secular society in Europe, passing through the Protestant Reform, through immigration to America, and to the current situation of the Brazilian church, to which is also offered a brief psychotheological analysis. In the second part, once-established similarities to the churches in Galatia from the Biblical epistle times, we move on to study the historical context of these recipients, and proceed to an exegesis of Gl 3.1-5, which synthesizes Paul s reaction to the fascination of those Christians towards obeying laws and duties. We then see how he puts this attitude of them in contrast with the gospel originally presented by him, based on the preaching of the faith, on the centrality of the cross of Jesus, and on life in the freedom of the Holy Spirit. To better understand this opposition of two lifestyles before God, in this work we follow the unrolling of the path of the Spirit along the whole Epistle, searching in more detail what the burden of Christian duty is made of, and how God s Word tries to encourage us to follow the free, loving, and fruitful way of the Spirit. In conclusion, we list the elements perceived, and noticing the possibility of a different understanding of duty, we make way for invitations to the current Church to deepen itself in the lane of the Spirit.